Quantitative trait loci for performance traits in a broiler x layer cross - Ambo, M.; Moura, Ana Silvia Alves Meira Tavares [UNESP]; Ledur, M. C.; Pinto, L. F. B.; Baron, E. E.; Ruy, D. C.; Nones, K.; Campos, R. L. R.; Boschiero, C. [UNESP]; Burt, D. W.; Coutinho, L. L. (Wiley-Blackwell Publishing, Inc, 2009)
An F(2) resource population, derived from a broiler x layer cross, was used to map quantitative trait loci (QTL) for body weights at days 1, 35 and 41, weight gain, feed intake, feed efficiency from 35 to 41 days and intestinal length. Up to 577 F(2) chickens were genotyped with 103 genetic markers covering 21 linkage groups. A preliminary QTL mapping report using this same population focused exclusively on GGA1. Regression methods were applied to line-cross and half-sib models for QTL interval mapping. Under the line-cross model, eight QTL were detected for body weight at 35 days (GGA2, 3 and 4), body weight at 41 days (GGA2, 3, 4 and 10) and intestine length (GGA4). Under the half-sib model, using sire as common parent, five QTL were detected for body weight at day 1 (GGA3 and 18), body weight at 35 days (GGA2 and 3) and body weight at 41 days (GGA3). When dam was used as common parent, seven QTL were mapped for body weight at day 1 (GGA2), body weight at day 35 (GGA2, 3 and 4) and body weight at day 41 (GGA2, 3 and 4). Growth differences in chicken lines appear to be controlled by a chronological change in a limited number of chromosomal regions.
Keywords: chicken; feed efficiency; growth; intestine length; quantitative trait loci